Location Preferences of New Pedestrian Bridges Based on Multi-Criteria Decision-Making and GIS-Based Estimation - Jurgis Zagorskas; Zenonas Turskis (The Baltic Journal of Road and Bridge Engineering, 2020)
Non-motorized pedestrian and bicycle traffic is an effective and efficient tool for reducing the negative environmental impacts of transport and improving the quality of life in urban conditions. The strategies of creating new attractive spaces on the waterfront are prevalent amongst the municipalities in different countries. This kind of development intends the construction of new connection bridges, usually meant solely for walking and cycling. There are a significant number of studies covering the theme of pedestrian bridges, but the studies typically focus on technical parameters – serviceability, stress and vibrations, specifications for the design. Researchers and stakeholders rarely discuss displacement strategy, expenditure and future usability. This study aims to find out the best and the most useful bridge locations that would contribute to pedestrian network improvement, would add value to city image and give other benefits. A novel hybrid Multi-Criteria Decision-Making (MCDM) model, based on five different multi-criteria decision-making methods: Multiplicative Exponential Weighting (MEW), method of Evaluation Based on Distance from Average Solution (EDAS), an Additive Ratio Assessment (ARAS) method, expert judgement, and Step‐Wise Weight Assessment Ratio Analysis (SWARA), is presented. A developed model allows solving complicated problems and finding a rationally, balanced solution. Arguments derived from this study help politicians and town planners as well as society.